Development of Media Activity Books to Overcoming Reading Difficulties in Children With Special Needs - Nurmala Hidayati; Roni Amrulloh; Abdul Aziz (IJE : Interdisciplinary Journal of Education, 2023)
This researchers use Activity Book media as a learning medium that can be used to improve reading skills in ABK (Children with Special Needs) students. This research was conducted with the aim of developing Activity Book media for ABK students (Children with Special Needs) who have reading difficulties or are called dyslexics using the Borg and Gall research design which consists of 10 steps which are then simplified into 7 steps namely (1) research and data collection, (2) planning, (3) product development, (4) initial field trials, (5) learning media revision, (6) main product testing, (7) final product. This research was conducted on a grade 4 student who had difficulty reading. This research uses Research and Development approach. The research instrument used media expert validation sheets, material expert validation sheets and principal responses. The results of the media expert validation test get a score of 99 and are in the range of scores X> 96.54 with the category "very good" and the results of the validation of material experts get a score of 38 which is in the range of scores x> 33.54 with the category "very good" good” while the results of the principal's response obtained a score of 70 and were in the range of scores X> 63 in the "very good" category. It can be concluded that the Activity Book media is valid and effective as a tool that makes it easier for students to overcome reading difficulties.